Welfare Measures and Ecological Footprint as Spatial Sustainability Indicators - Kurt Kratena; Gerhard Streicher (Austrian Institute of Economic Research (WIFO), 2009)
The aim of this paper is to compare a social welfare (SW) indicator for sustainability with the ecological footprint (EF) indicator for measuring spatial sustainability. The framework applied follows the line of a core-periphery model of "new economic geography" as put forward in Grazi, van den Bergh and Rietveld, EnvironResourceEcon, 2007, (38) with interregional trade, agglomeration advantages and resource (land) use or environmental externalities. Welfare or sustainability indicators rely on quantitative relations between economic welfare, externalities and the integrity of (global) natural capital. We argue that these relationships, in order to be comparable, should be specified in a similar way in both indicator concepts (SW function and EF). The main difference between the two indicators is that the EF concept works with a binding resource constraint ("biocapacity") and therefore exclusively represents strong sustainability, while the SW indicator can be specified in a way to represent strong as well as weak sustainability. If the SW function is specified and parameterised as an indicator for strong sustainability, we get similar results for the welfare ranking of different land use configurations. If the SW function is specified and parameterised as an indicator for weak sustainability, we replicate the results of Grazi, van den Bergh and Rietveld (2007) that EF and SW lead to completely different welfare rankings of different land use configurations.
Keywords: 330; ecological footprint; social welfare measures; weak and strong sustainability; Umweltbelastung; Nachhaltige Entwicklung; Sozialer Indikator; Zentrum-Peripherie-Beziehungen; Neue ökonomische Geographie